A Comparison of the Electrical Properties of Gel Polymer Electrolyte-Based Supercapacitors: A Review of Advances in Electrolyte Materials - Ghobad Behzadi Pour; Hamed Nazarpour Fard; Leila Fekri Aval (Gels)
Flexible solid-state-based supercapacitors are in demand for the soft components used in electronics. The increased attention paid toward solid-state electrolytes could be due to their advantages, including no leakage, special separators, and improved safety. Gel polymer electrolytes (GPEs) are preferred in the energy storage field, likely owing to their safety, lack of leakage, and compatibility with various separators as well as their higher ionic conductivity (IC) than traditional solid electrolytes. This review covers the classification, properties, and configurations of different GPE-based supercapacitors and recent advancements that have occurred in this area of energy storage. Ionic liquid (IL)-based materials are popular GPEs for electrochemical energy storage and can be used to prepare unprecedented flexible supercapacitors due to their great IC and wide potential range. A comparative assessment of the GPEs-based supercapacitors reveals that in a majority of them, the value of specific capacitance is generally under 1000 F g−1, energy density reaches around 125 Wh kg−1, and the power density is seen to be less than 1500 W kg−1. The results of this research serve as an essential reference for upcoming scholars, and could significantly improve our comprehension of the efficacy of GPE-containing supercapacitors.